The Changing View of Grammar Instruction - Nassaji, Hossein; Fotos, Sandra S. (Teaching Grammar in Second Language Classrooms, 2011)
Grammar is fundamental to language. Without grammar, language does not exist. However, nothing in the ﬁeld of language pedagogy has been as controversial as the role of grammar teaching. The controversy has always been whether grammar should be taught explicitly through a formal presentation of grammatical rules or implicitly through natural exposure to meaningful language use. According to Kelly (1969), this controversy has existed since the beginning of language teaching. However, whatever position we take regarding grammar instruction, “it is bound to be inﬂuenced by the recent history of grammar teaching” (Stern, 1992, p. 140). Therefore, to provide a background to the book, we begin by providing a brief overview of the changes in the teaching of grammar over the years.